Top-ten tips for managing nutritional issues and gastrointestinal symptoms in children with neurological impairment - Valeria Dipasquale; Frederic Gottrand; Peter B. Sullivan; Claudio Romano (BMC, 2020)
Abstract The prevalence of children with neurological impairment (NI) presenting feeding difficulties and gastrointestinal symptoms is rising. The most recent guidelines recommend early nutritional assessment and intervention in order to prevent undernutrition and growth failure, along with the proper diagnosis and treatment of some frequent gastrointestinal symptoms, such as gastroesophageal reflux disease (GERD) and constipation, which can further worsen the feeding process and nutritional status. Nonetheless, the nutritional issues and growth deficits of children with NI are often considered to be of low priority or under recognised by healthcare providers. The present article proposes ten top tips that highlight the major points along the nutritional management pathway of NI children. The implementation of these tips in all healthcare settings could potentially improve patient outcomes and reduce morbidity and mortality.